PENGARUH PERMAINAN TEBAK KARTU EKSPRESI TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK AISYIAH BUSTANUL ATFHAL PULAU BANJAR - DESPERA AYU; Wilson '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the emotional intelligence of the students is still low and teachers are still using methods that dominate and less varied. So that needs to be given in the form of learning games that can increase a child's imagination. This study aims to determine the effect of a card guessing game images expression of the emotional intelligence of children aged 5-6 years in kindergarten Aisyiyah Bustanul Atfhal Banjar Island. The sample used in this study were 17 children. The data collection techniques were used that observation. Data were analyzed using t-test with using SPSS version 20. The study hypothesis was availability a significant effect on emotional intelligence after applying the card guessing game image expression. It can be seen from the analysis of data obtained t = 18.98 and p = 0.055. Because p <0.05 it can be concluded that differences in emotional intelligence there is protege significant after applying the graphics card guessing game of learning in carrying expression. So it means Ho rejected and Ha accepted which means no significant difference between before and after performing experiments by applying a guessing game card image expression. As for the influence of the graphics card guessing game against the expression of emotional intelligence in children aged 5-6 years tk Aisyiyah Bustanul Atfhal Banjar Island is the (p) = 0.37%.